2018
DOI: 10.1016/j.physbeh.2018.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Eating in the absence of hunger: Stability over time and associations with eating behaviours and body composition in children

Abstract: EAH is a stable behavioural risk factor for increased energy intake, but was not associated with body composition in this cohort. The majority of children ate in the absence of hunger, suggesting that interventions aimed at reducing responsiveness to external food cues could help to reduce energy intakes. Trial Registry Number: NCT01174875; https://clinicaltrials.gov/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 49 publications
1
18
2
Order By: Relevance
“…Due to possible variation between mothers and perhaps clarity of child satiety cues, this procedure may also have introduced variability. However, a recent study showed that the amount consumed during the EAH task was not associated with how much children ate during lunch, suggesting that EAH intake in our study also may not be simply a compensatory mechanism among children who consumed less at lunch (Fogel et al, 2018). Nonetheless, future research may consider assessing EAH on multiple days to obtain more stable estimates.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Due to possible variation between mothers and perhaps clarity of child satiety cues, this procedure may also have introduced variability. However, a recent study showed that the amount consumed during the EAH task was not associated with how much children ate during lunch, suggesting that EAH intake in our study also may not be simply a compensatory mechanism among children who consumed less at lunch (Fogel et al, 2018). Nonetheless, future research may consider assessing EAH on multiple days to obtain more stable estimates.…”
Section: Discussioncontrasting
confidence: 69%
“…This is consistent with prior studies (Garcia et al, 2016; Mallan et al, 2014), in which maternal reports of child FR or SR were not associated with EAH. Our findings further illustrated that mother-reports at 27 months did not relate to EAH across time, suggesting that although FR has been identified as a type of food approach behavior that may confer obesity risk (Fogel et al, 2018; Lansigan et al, 2015), EAH may not be the process that explains the link between maternal report of child FR or SR and obesity. Even though our finding of no association between mother-reported child eating and EAH was consistent with prior work, more research is needed to unpack these processes during the toddler age period.…”
Section: Discussionsupporting
confidence: 50%
“…[41][42][43][44] This study also provides new evidence of neuronal correlates of disinhibited eating behaviours in this young age group, indicating that alterations in executive control, salience, reward, and default network functional circuitry begin early in the life course and may underlie the risk for later life obesity via overeating. The results of the current study confirm observations made by prior studies in which hedonically motivated disinhibited eating behaviours were documented in young children, 3 to 6 years old.…”
Section: Discussionmentioning
confidence: 60%
“…The results of the current study confirm observations made by prior studies in which hedonically motivated disinhibited eating behaviours were documented in young children, 3 to 6 years old. [41][42][43][44] This study also provides new evidence of neuronal correlates of disinhibited eating behaviours in this young age group, indicating that alterations in executive control, salience, reward, and default network functional circuitry begin early in the life course and may underlie the risk for later life obesity via overeating. Furthermore, some evidence suggests that EAH, as a specific disinhibited eating behaviour, is stable over time.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation